Fundamentals of Financial Statements Audit - World Bank (Washington, DC, 2013)
The purpose of an audit is to enhance the degree of confidence of intended users in the financial statements. The objective of an audit of financial statements is to enable an auditor to express an opinion as to whether the financial statements are prepared, in all material respects, in accordance with International Financial Reporting Standards or another identified financial reporting framework. The auditor's opinion is expressed in by using the phrase 'give a true and fair view' or 'present fairly, in all material respects'. The auditor and the client's management have separate and distinct responsibilities. The auditor is responsible for forming and expressing an opinion on the financial statements. The client's management, on the other hand, bears responsibility for preparing and presenting the financial statements. Management's responsibilities are not relieved by the fact that the statements are audited. An auditor must comply with general principles of an audit. These require an auditor to: 1) comply with the 'Code of Ethics for Professional Accountants' issued by the IFAC (or a national Code of Ethics, where appropriate); 2) conduct an audit in accordance with International Standards on Auditing (ISAs) (where applicable); and 3) plan and perform the audit with an attitude of professional skepticism, recognizing that circumstances may exist that cause the financial statements to be materially misstated.